Naturally occurring circadian rhythm and sleep duration are related to executive functions in early adulthood. (20th July 2017) - Kuula, Liisa; Pesonen, Anu‐Katriina; Heinonen, Kati; Kajantie, Eero; Eriksson, Johan Gunnar; Andersson, Sture; Lano, Aulikki; Lahti, Jari; Wolke, Dieter; Räikkönen, Katri
Summary: Experimental sleep deprivation studies suggest that insufficient sleep and circadian misalignment associates with poorer executive function. It is not known whether this association translates to naturally occurring sleep patterns. A total of 512 of full‐term‐born members of the Arvo Ylppö Longitudinal Study [mean age = 25.3, standard deviation (SD) = 0.65] (44.3% men) wore actigraphs to define sleep duration, its irregularity and circadian rhythm (sleep mid‐point) during a 1‐week period (mean 6.9 nights, SD = 1.7). Performance‐based executive function was assessed with the Trail‐Making Test, Conners' Continuous Performance Test and Stroop. The self‐rated adult version of Behavior Rating Inventory of Executive Function was used to assess trait‐like executive function. We found that performance‐based and self‐reported trait‐like executive function correlated only modestly (all correlations ≤0.17). Shorter sleep duration associated with more commission errors. Later circadian rhythm associated with poorer trait‐like executive function, as indicated by the Brief Metacognitive Index and the Behavior Regulation Index. Those belonging to the group with the most irregular sleep duration performed slower than others in the Trail‐Making Test Part A. All associations were adjusted for sex, age, socioeconomic status and body mass index. In conclusion, naturally occurring insufficient sleep and later circadian rhythm showed modest associations with poorer executive function. Shorter habitual sleep duration was associated with lower scores of performance‐based tests of executive function, and later circadian rhythm was associated mainly with poorer trait‐like executive function characteristics. Our findings suggest additionally that sleep duration and circadian rhythm associate with different domains of executive function, and there are no additive effects between the two.